2010
DOI: 10.3362/1755-1986.2010.028
|View full text |Cite
|
Sign up to set email alerts
|

Emerging guidelines for linking youth to financial services

Abstract: Access to appropriate financial services can play a critical role in enabling young people to navigate the challenges and opportunities they face, regardless of their employment or educational status. This paper discusses: 1) the results of a global survey conducted in 2009 by Making Cents International; and 2) findings of leading NGOs and financial institutions which are pioneering youth-inclusive and youth-specific financial products. The outcomes of the survey findings and lessons learned have been synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…These associations were decomposed by program inputs. As is consistent with literature elsewhere and with common practice, material inputs of cash (Adato & Bassett, ), and a start‐up kit to begin a small business (DaJaeghere & Baxter, 2014; Storm, Porter, & Macaulay, ) predicted increased monthly income. Cash transferred, reported monthly income, and food consumption completely mediated the association between program participation and savings in the past year.…”
Section: Discussionsupporting
confidence: 85%
“…These associations were decomposed by program inputs. As is consistent with literature elsewhere and with common practice, material inputs of cash (Adato & Bassett, ), and a start‐up kit to begin a small business (DaJaeghere & Baxter, 2014; Storm, Porter, & Macaulay, ) predicted increased monthly income. Cash transferred, reported monthly income, and food consumption completely mediated the association between program participation and savings in the past year.…”
Section: Discussionsupporting
confidence: 85%
“…This is especially true for low-income youth who may lack the knowledge or social networks to access these services, or even the legal right to do so. Storm, Porter, and Macaulay (2010), in a global survey of financial service providers and youth-service organizations, found that regulatory systems inhibited youth from accessing financial services (p. 321). Because the vast majority of regulatory systems only allow those of legal age to open a bank account, minors usually lack independent access to bank financing.…”
Section: Regulatory Environmentmentioning
confidence: 97%
“…Such areas are usually difficult to access. The level of access is also impacted by limited competition within concentrated market areas, which lowers incentives for lending institutions to explore such market areas (Storm, Porter & Macaulay, 2010). Low-income people and small firms are usually limited of information or credit histories regarding their financial operations.…”
Section: Income Statusmentioning
confidence: 99%